Prevalence of Buxtonella sulcata in Sheep and Supplied drinking water - Makawi, Zainab A. (The Iraqi Journal of Veterinary Medicine, 2019)
Buxtonella sulcata multiplication in lumen of the intestinal tract lead to Diarrhea. A total of 120 sheep faecal samples were collected (23 males and 97 females) with ages ranged from less than 1 year to 3 years. Also, 11 sheep drinking (river) water from Al-Suwaira city, Wasit governorate, for the period extended from September 2015 to the end February 2016. Laboratory methods used were direct wet film and iodine and Giemsa staining to detect the cysts and trophozoite of the parasite . Results recorded (30.83%) infection rate of Buxtonella sulcate in sheep, while the contamination rate of water (45.45%). Females are infected more than males which reach (35.13%) (13.04%) respectively. The highest infection rate (44.00%) showed in age group 2-3 years, while, the lowest (21.42%) found in age group (˃ 2). %), with significant difference (p<0.05) between ages and genus. Our conclusion is contamination of water acts as a good sourse for the spread of infection with Buxtonella sulcate .